One Piece : East Blue Part 1 (Vol 1) Vol. 1, East blue. part 1, Romance Dawn - Oda, Eiichiro, 1975- (San Francisco, California : VIZ Media, 2003)
When Monkey D. Luffy accidentally gains the power to stretch like rubber at the cost of never being able to swim again, he and his crew of pirate wannabes set off in search of the "One Piece," the greatest treasure in the world.
"This volume contains material that was originally published in English in Shonen Jump #1-4, plus the first One piece episode in Shonen Jump #5"--T.p. recto.
"First published in Japan in 1997 by Shueisha Inc, Tokyo"- -T.p recto.
"East blue part 1"--P. [4] of cover.
"Parental advisory ... recommended for ages 13+ ... contains fantasy violence and tobacco use."--T.p. recto.
"This book reads from right to left"--P. [4] of cover.
Rated T for teen.
Keywords: Pirates -- Comic books, strips, etc; Treasure troves -- Comic books, strips, etc; Comic books, strips, etc. -- Japan; Translations into English; Graphic novels -- Japan; Translations into English; Pirates -- Fiction; Treasure troves -- Fiction; Pirates -- Fiction; Buried treasure -- Fiction; Buried treasure -- Comic books, strips, etc; Cartoons and comics -- Japan; Translations into English; Comic books, strips, etc. -- Japan; Graphic novels -- Japan